Media Video Promosi Pada Roofpark Cafe & Restaurant Pucak Bogor Jawa Barat - Sunarya, Lusyani; Purbayani, Ayunda Dwi; Handayani, Nadya (Technomedia Journal, 2021)
ABSTRACT Current promotional activities are very important to introduce a product or service to increase the appeal of the wider community. Previously Roofpark Café & Restaurant only used simple video vlogs, websites, and used several printed media in the form of brochures, banners and newspaper media. So that the promotion media is not right, the information is still incomplete in informing the latest developments. Roofpark Café & Restaurant is a café that has an instagramble and garden concept. Roofpark Café & Restaurant is located on Jl. Raya Cimacan, Palasari, Kec. Cipanas, Cianjur Regency, West Java. Current problems require the design of promotional video media with more complete, updated and interesting information. So there is a need for promotional videos through social media and YouTube, so that it can increase the target of visitors every year and can be known to the wider community. The research method is to use data collection methods, SWOT analysis, media design, and the concept of media production (KPM), namely pre production, production, and postproduction. The results of this research are in the form of promotional video media for Roofpark Café & Restaurant which is expected to attract public interest in Roofpark Café & Restaurant. Keywords ___ Promotion Video, Information, Restaurant